Editorial for the Special Issue “Remote Sensing Monitoring of Land Surface Temperature” - Juan M. Sánchez; César Coll; Raquel Niclòs (Remote Sensing, 2021)
The combination of the state-of-the-art in the thermal infrared (TIR) domain [...]